2016
DOI: 10.18295/squmj.2016.16.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Khat ( Catha edulis ) Use on the Bioavailability, Plasma Levels and Antimalarial Activity of Chloroquine

Abstract: abstract:Objectives: This study aimed to evaluate the effect of khat (Catha edulis) on chloroquine (CQ) bioavailability in healthy Yemeni adults and its effect on CQ plasma levels and parasite clearance among malaria patients. Methods: This study took place between January and April 2007 in Bajil and Sana'a, Yemen. Two CQ doses (600 mg each) were given to 15 healthy males on separate occasions; the first dose was followed by a khat-chewing session (phase one) while controls abstained from khat-chewing for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Furthermore, a previous study reported no significant inhibition of CYP2D6 by chloroquine in human (Masimirembawa et al, 1996). Thus, khat-chloroquine interaction reported by Issa et al (2016), may not be at the CYP2D6 level. Nevertheless, concomitant khat use may compromise the antimalarial activity of primaquine.…”
Section: Antimalarial Drugsmentioning
confidence: 90%
See 1 more Smart Citation
“…Furthermore, a previous study reported no significant inhibition of CYP2D6 by chloroquine in human (Masimirembawa et al, 1996). Thus, khat-chloroquine interaction reported by Issa et al (2016), may not be at the CYP2D6 level. Nevertheless, concomitant khat use may compromise the antimalarial activity of primaquine.…”
Section: Antimalarial Drugsmentioning
confidence: 90%
“…In Yemen, it was reported that the coadministration of chloroquine (CQ) and khat was found to significantly affects the pharmacokinetics of CQ among both healthy controls and malaria patients and significantly reduces plasma CQ concentrations in malaria patients (Issa et al, 2016). At therapeutic concentration, chloroquine is metabolized into desethylchloroquine primarily by CYP2C8 (60%) followed by CYP3A4 (25%), and CYP2D6 is a high affinity but with significantly low-capacity enzyme to metabolize chloroquine (Projean et al, 2003).…”
Section: Antimalarial Drugsmentioning
confidence: 99%
“…Indeed, the primaquine’s metabolite, which is responsible for hypnozoite killing, is also generated by CYP2D6 51 . A recent study by Issa et al ., in Yemen reported that Khat-chewing significantly reduces plasma chloroquine concentrations in malaria patients 28 . However, the authors did not control for the amount of Khat used and the timing of the Khat-chewing sessions in relation to chloroquine administration.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the regular use of Khat by millions of people for centuries, little is known about the potential Khat-drug interactions. Few studies in Yemen reported that Khat chewing significantly reduced the bioavailability of ampicillin and chloroquine 27 , 28 but the mechanism behind these observations remain unknown. In a small sample size preliminary study, we recently reported a significant inhibition of CYP2D6 and a borderline effect on CYP3A4 metabolic activity by Khat use 29 .…”
Section: Introductionmentioning
confidence: 99%
“…3 It also affects the therapeutic effects of drugs. 4 , 5 Certain disease conditions are aggravated by CEF . 6 , 7 Cathinone, Cathine, tannins, ascorbic acid (AA), and electrolytes are some of the composites in it.…”
Section: Introductionmentioning
confidence: 99%